Profil als Prozess: Grundzüge eines diakonischen Profildialogs - Liedke, Ulf (Pastoraltheologie, 2015)
Profile as a Process: Main Features of a Diaconical Profile Dialogue. Using insights from the St. Gallen concept of organisational communication and from the “index for inclusion” developed by the “Enabling Education Network”, the author presents a concept of the basic categories and indicators for a diaconic profile dialogue in Protestant social service organisations.